Evaluating the Impact of Integrated Digital Marketing on Homestay Success in India : A Study of Uttarakhand - Dutta, Dipankar; Amir, Mohd (Indian Journal of Marketing, 2025)
Purpose : With the growing prevalence of digital literacy, most businesses are increasingly utilizing digital marketing. Moreover, homestays have become an integral part of the community-based tourism industry. This study aimed to investigate the impact of various digital marketing tools on the success of homestays in Uttarakhand, India, and to test a theoretical model for predicting the success of homestays. Methodology : The study proposed an integrated research model of “Homestay Success” in which “email,” “travel booking website,” “social media,” and “electronic word of mouth” were identified as independent latent variables. A total of 309 responses were collected from various homestay owners in Dehradun, Haridwar, Nainital, Tehri-Garhwal, and Uttarkashi districts of Uttarakhand, using a structured questionnaire, and analyzed using Smart-PLS. Findings : We found that all four independent variables significantly influenced the success of the “Homestay.” In addition to validating the theoretical model, the study contributed to the existing literature on community-based tourism (CBT). Practical Implications : The study recommended that stakeholders in CBT, including government agencies, local communities, policymakers, and homestay hosts, should compare their current business models with the model proposed in this study to identify areas for improvement and adopt more effective strategies for necessary enhancements. According to the Importance Performance Map Analysis (IPMA), “electronic word of mouth” was crucial for the success of the homestays ; it had been underperforming and needed managerial attention to improve. Homestay owners should focus on enhancing “electronic word of mouth” by participating in workshops and implementing strategies to boost its effectiveness. Originality : Unlike previous studies on the factors influencing Homestay Success (HS), the present research developed a model to explore the role of integrated digital marketing in enhancing HS.